Image Segmentation for Environmental Monitoring - Johnson, Brian Alan; Ma, Lei (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
OBIA, based on image segmentation and as an important remote sensing monitoring technology, has been widely used in forestry, vegetation, wetland, urban, crop, conservation, ecology, and agriculture areas. Although OBIA has considerably progressed in the past 20 years, OBIA still much room for further development, regardless of the technological aspect of OBIA or the prospective expansion field of applications. Therefore, this book was organized to further encourage OBIA technology development and expand OBIA applications. This book collects a total of eight papers, which compile the current state-of-the-art research and technology in the area of image segmentation, and highlight prominent current application directions. Therefore, this book not only contains innovative methods, but also covers the innovation of application-driven OBIA technology. The eight papers in this highlight both the popular applications (urban, vegetation, ecology) and several subjects that require additional research attention (landslide, arid-land).